Optimising Human Resource Management in Community Empowerment Programs: A Case Study in a Rural Community - Riyadi, Slamet; Alimuddin, Alimuddin; Fitriani, A.; Iswanto, Iswanto; Supendi, Dede (Civiliza Publishing, 2025)
This study investigates the critical role of Human Resource Management (HRM) in enhancing community empowerment initiatives within rural settings. By employing a qualitative methodology, the research explores various HRM strategies implemented in selected rural communities, focusing on their effectiveness in fostering local capacity building and sustainable development. Through in-depth interviews and focus group discussions with community stakeholders, the study identifies key HRM practices that contribute to improved socio-economic outcomes. The findings reveal that tailored HRM interventions significantly enhance skills development, promote active community participation, and facilitate better resource management. Furthermore, this research highlights the importance of integrating local knowledge and cultural contexts into HRM practices to ensure their relevance and effectiveness. The implications of these findings suggest that optimizing HRM can lead to more successful community empowerment programs, ultimately contributing to enhanced quality of life for rural populations.